Circulation and consumption of the brazilian telenovela Salve Jorge: the case of Maria Vanúbia on Twitter (Novos Olhares, 2015)
With the objective of reflecting on the simultaneous use of television andTwitter, the text articulates Pêcheux’s discourse analysis with Bourdieu’s sociologyto capture the workings of the imagination: the ways in which a character appearsin the telenovela and as it is commented by the public/audience on Twitter.Selected comments on the telenovela Salve Jorge (Rede Globo 2012/2013) thatmention the character Maria Vanúbia, role of actress Roberta Rodrigues, areconstitutive elements of the research. As a result, we conclude that the successof the character in Twitter is related with the class distinction.